Pengaruh Kepemimpinan Otentik terhadap Keterlibatan Karyawan pada PT. Europlast Fenster Indonesia - Wilson Sorip; Rokhmad Slamet; Dewi Listiorini (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
Employee engagement is a critical factor in enhancing organizational performance and sustainability amid global competition. The decline in engagement levels within the manufacturing sector highlights the need for leadership that can foster strong work commitment. This study aims to analyze the effect of authentic leadership on employee engagement at PT. Europlast Fenster Indonesia. This research employed a quantitative associative approach using a survey of 150 permanent employees selected through purposive sampling. The instrument used was the Authentic Leadership Questionnaire (Walumbwa et al., 2008), and the data were analyzed using linear regression with SPSS version 25. The results indicate that authentic leadership has a positive and significant effect on employee engagement, meaning that higher levels of transparency, integrity, and balanced decision-making by leaders are associated with higher employee engagement. Practically, organizations should develop leadership training programs focused on self-reflection, honesty, and open communication to sustainably strengthen employee engagement.